2021
DOI: 10.1371/journal.pmed.1003719
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-informed policy for tackling adverse climate change effects on health: Linking regional and global assessments of science to catalyse action

Abstract: Effective policy making depends on synthesising and improving the use of existing robust scientific evidence, tackling misinformation, and identifying knowledge gaps to be filled by new research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This finding adds to the much-debated concern in climate change about the disparities between and within regions in terms of contribution and vulnerabilities to the effects of climate change [40]. Coordinated policy development approaches across sectors and regions and integration at national/regional/global levels are essential to understand trade-offs, avoid inadvertent consequences, and capitalize on potential synergies for multiple benefits for health, equity, and the environment [41]. Information gaps from LMICs could make it difficult to draw valuable conclusions about successful (and unsuccessful) strategies across multiple, varying contexts.…”
Section: Underrepresentation From Low-and Middle-income Countries (Lm...mentioning
confidence: 85%
“…This finding adds to the much-debated concern in climate change about the disparities between and within regions in terms of contribution and vulnerabilities to the effects of climate change [40]. Coordinated policy development approaches across sectors and regions and integration at national/regional/global levels are essential to understand trade-offs, avoid inadvertent consequences, and capitalize on potential synergies for multiple benefits for health, equity, and the environment [41]. Information gaps from LMICs could make it difficult to draw valuable conclusions about successful (and unsuccessful) strategies across multiple, varying contexts.…”
Section: Underrepresentation From Low-and Middle-income Countries (Lm...mentioning
confidence: 85%
“…To ensure that potential studies are not missed, we will apply an iterative approach using known studies that meet the inclusion criteria identified during the preparation of the protocol. Three examples of studies meet the inclusion criteria for the current scoping review: Tchoukaleyska et al ., 2021 [ 27 ] Fears et al ., 2021 [ 28 ], and Lapaige and Essiembre, 2010 [ 29 ]. Studies that meet the inclusion criteria will be searched for among “hits” (search records) and used to identify new keywords and MeSH terms not already included in the search strategy.…”
Section: Identifying Relevant Studiesmentioning
confidence: 99%
“…The detrimental impact of human activity on the environment – in terms of climate change, natural resource depletion, and biodiversity loss – is now undeniable and requires urgent intersectoral action (1). Environmental degradation and climate change threaten the foundations of good health, with direct and immediate consequences for population health and, hence, health systems (2).…”
Section: Introductionmentioning
confidence: 99%